The Role Of The Creative Economy In Increasing The Competitiveness Of Cirebon Msmes In The Digital Era - Fatimah, Siti Eva (Fakultas Ekonomi Universitas Gresik, 2025)
The Creative Economy has emerged as a powerful tool to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs), particularly in Cirebon, where digitalization is rapidly taking place. As MSMEs in Cirebon face the challenge of adapting to digital markets, the role of digital marketing, e-commerce, and innovative product design through creative economy principles has become crucial. This study aims to investigate how creative economy practices can improve the competitiveness of MSMEs in Cirebon in the digital era. Using a qualitative research approach and a literature review of previous studies, this research identifies the main factors that contribute to the successful adoption of digital technologies by MSMEs in Cirebon. The findings indicate that creative economy practices, particularly in digital marketing and product innovation, significantly enhance market access and sales performance. However, challenges such as digital skills gaps and limited access to technology remain obstacles. The study concludes with recommendations for improving policy support, training programs, and collaborations between sectors to boost the adoption of creative economy principles and digitalization for MSMEs.